An experimental analysis of the impact of campaign polls on electoral information seeking. (December 2015) - Roy, Jason; Singh, Shane P.; Fournier, Patrick; Andrew, Blake
Abstract: The literature on poll effects has focused upon the impact polls have on election outcomes. To understand how polls affect information seeking more broadly, we examine the influence of campaign-period polls on the decision-making process. Based on an online voting experiment, we find that poll exposure affects information seeking, albeit under limited conditions, and that this effect is mediated according to voters' sophistication levels. Results also indicate that party-specific deliberation can also be influenced by poll standings; candidates from parties trailing in the polls receive less attention than the leading party, although this is also conditional upon the size of the lead. We then consider how these effects on the information calculus influence voting behavior, finding a bandwagon effect when a clear front-runner is depicted in the polls. Highlights: Poll exposure affects information seeking, albeit under limited conditions; this effect is mediated by sophistication. Party-specific deliberation can also be influenced by poll standings, although this is conditional upon the size of the lead. Individuals who limited their deliberation process were more likely to support the frontrunner with their votes.